Efficacy and safety of external-beam radiation therapy for hepatocellular carcinoma: An overview of current evidence according to the different target population - Han, Bing; Li, Chuan; Meng, Hao; Romeiro, Fernando Gomes [UNESP]; Mancuso, Andrea; Zhou, Zhirui; Sandri, Giovanni Battista Levi; Xu, Ying; Han, Tao; Han, Lei; Shao, Lichun; Qi, Xingshun (International Research and Cooperation Association for Bio & Socio-Sciences Advancement (IRCA-BSSA), 2019)
Hepatocellular carcinoma (HCC) is one of the most common malignant tumors. During the recent years, external-beam radiation therapy (EBRT) has been safely and effectively employed for the management of HCC. We overviewed the current evidence regarding the efficacy and safety of EBRT for HCC according to the different target population. PubMed database was searched for identifying English-language full-text articles regarding EBRT for the treatment of HCC. Search items were hepatocellular carcinoma AND radiation therapy. Until now, preliminary evidence has suggested the following role of EBRT for HCC. 1) EBRT, especially stereotactic body radiation therapy, is an emerging choice of therapy for small HCC. 2) EBRT combined with non-surgical treatment can achieve an excellent intrahepatic tumor control and a potential survival benefit for huge HCC. 3) Adjunctive EBRT may improve the efficacy of transarterial chemoembolization for HCC with portal vein tumor thrombosis. 4) EBRT can relieve the pain and improve the quality of life for patients with extrahepatic metastases. 5) EBRT may be a bridge to liver transplantation by minimizing the tumor progression. 6) Adjunctive EBRT may reduce the tumor recurrence and improve the survival after resection. In summary, EBRT is a promising choice of treatment of HCC. However, more high-quality evidence is needed to further establish the status of EBRT for the management of HCC.
Keywords: Evidence; Liver cancer; Radiation therapy; Survival